Human endothelial and platelet septin SEPT11: Cloning of novel variants and characterisation of interaction partners - Bartsch, Ingrid; Bläser, Susanne; Röseler, Sabrina; Sandrock, Kirstin; Busse, Anja; Huber, Michael; Rempp, Hansjörg; Lieber, Mareike; Horn, Julia; Brendle, Cornelia; Zieger, Barbara (Thrombosis and Haemostasis, 2010)
Septins are cytoskeletal GTPases forming heteropolymeric complexes involved in processes characterised by active membrane movement such as cytokinesis, vesicle trafficking, and exocytosis. Septins are expressed in non-mitotic cells such as neurons and platelets. SEPT11 belongs to the SEPT6 group and was identified as interaction partner of SEPT5. We cloned and characterised novel SEPT11 variants and investigated interaction partners of SEPT11 in platelets and human umbilical vein endothelial cells. An endothelial cell library was used for cloning novel SEPT11 variants. Using Northern analysis the different SEPT11 transcripts were illustrated. Interaction studies were performed using yeast two-hybrid system, precipitation, FRET, and immunofluorescence microscopy. We demonstrate that SEPT11 partners with SEPT2, SEPT4 and SEPT7 using yeast two-hybrid system and precipitation. The interaction of SEPT11 with SEPT7 is also demonstrated by FRET. In addition to the known SEPT11 transcript (SEPT11_v1) we identified a novel SEPT11 variant (SEPT11_v2) as interaction partner of SEPT4 and SEPT7. Library screening of an endothelial cell library also revealed the presence of this novel SEPT11_v2 transcript. In addition, a third SEPT11 variant (SEPT11_v3) was identified. Expression of SEPT11_v1 and of SEPT11_v2 and SEPT11_v3 in human brain regions was investigated by Northern analysis. Further interaction partners of SEPT11 are characterised using immunofluorescence. Co-localisation of SEPT2, SEPT4, SEPT7 and SEPT11 with tubulin and transferrin receptor (endocytotic marker) is demonstrated. In addition, co-localisation of SEPT4 and SEPT11 with the vesicle-associated protein synaptobrevin 1 (VAMP1), but not clearly with actin, was shown. Only SEPT2 and SEPT7 definitely co-localised with actin, but not clearly with VAMP1.
Keywords: Alternative splicing; cloning; HUVECs; platelets; SEPT11